VT stability tunnel: recommendations for CFD model validation in subsonic wind tunnels - Hoge Patil, Adwait; Roy, Christopher J.; Devenport, William J.; Borgoltz, Aurelien; Intaratep, Nanyaporn; Di Pasquale, Davide; Prince, Simon A. (American Institute of Aeronautics and Astronautics (AIAA), 2026)
The current work presents a computational fluid dynamics (CFD) investigation conducted under the NATO Applied Vehicle Technology framework to develop best practices for wind tunnel validation campaigns using the Virginia Tech Stability Wind Tunnel. The study is organized into two components, an empty-tunnel configuration, which forms the primary focus, and a preliminary model-in configuration featuring the Juncture Flow model. For the empty-tunnel case, a blind validation study was performed to identify and analyze discrepancies between CFD predictions and experimental measurements. Simulations of the as-built tunnel geometry characterize the spatial evolution of static pressure and quantify the influence of wall-induced pressure perturbations within the test section. A complementary investigation examines the flow differences observed under uniform versus non-uniform inflow boundary conditions, providing insight into the sensitivity of test-section pressure behavior to inflow characterization. The paper further consolidates best practices identified throughout the activity, covering meshing, boundary conditions, geometry, post-processing referencing, and experimental comparison. Preliminary model-in simulations incorporating the Juncture Flow geometry extend the investigation to examine the interaction between model-induced flow features and tunnel wall effects, providing initial validation results and identifying considerations relevant to model-in best practices. Insights from the study will contribute to the development of reliable, reproducible, and traceable best practices for wind tunnel validation campaigns.
Keywords: Applied Aerodynamics